Head-Waiter and Bridegroom of the Wedding at Cana: Structure and Meaning of John 2.1-12 - Bulembat, Jean-Bosco Matand (Journal for the study of the New Testament, 2007)
This study of the account of the wedding at Cana in Jn 2.1-12 was prompted by reactions to the manner in which Jesus addresses his mother as `Woman'. The literary structure of the pericope is analysed, and the roles of Jesus and his mother compared and contrasted with those of the bridegroom and head-waiter respectively. It is argued that Jesus is the true bridegroom and his mother the true head-waiter in this story, reflecting their status and roles in the divine dispensation. The connotations of `woman' need to be understood in their cultural context, and approximate those of `mother', the term of respect with which many African people address women in their societies.